The Integration of Islamic Epistemology and Science in Nurcholis Madjid’s Thought: A Conceptual Study - Firdah Ni’matus Sholihah; Indah Rahayu; Jamilatus Zahroh; Ita Yunita; Muhammad Fahmi; Miftahul Ulum; Sorhibulbahree Binmong (Fenomena, 2025)
Integrating science and religious knowledge is crucial in Islamic higher education, especially at UIN Sunan Ampel Surabaya, amid contemporary challenges that demand holistic approaches. While previous studies have addressed knowledge integration, few have explored its practical implementation in Islamic educational settings. This study investigates how Nurcholis Madjid’s thought contributes to integrating science and religion at this institution. Employing a qualitative approach with a literature review, data were collected from scholarly articles, books, and academic publications related to science-religion integration, focusing on Nurcholis Madjid’s perspectives. Data collection involved systematic searches across academic databases and libraries, followed by thematic analysis through coding, categorization, and synthesis to identify patterns supporting curriculum integration. The findings reveal that applying integration concepts at UIN Sunan Ampel enriches Islamic knowledge and cultivates students who are adaptive and responsive to modern developments. In conclusion, integrating science and religion enhances the relevance of Islamic education and promotes a more tolerant and inclusive society. Integrasi ilmu pengetahuan dan pengetahuan agama merupakan isu penting dalam pendidikan tinggi Islam, khususnya di UIN Sunan Ampel Surabaya, di tengah tantangan kontemporer yang membutuhkan pendekatan holistik. Meskipun studi sebelumnya telah membahas integrasi ilmu pengetahuan, sedikit yang mengeksplorasi implementasi praktisnya dalam lingkungan pendidikan Islam. Studi ini bertujuan untuk mengkaji bagaimana pemikiran Nurcholis Madjid berkontribusi pada integrasi ilmu pengetahuan dan agama di institusi tersebut. Dengan menggunakan metode kualitatif melalui tinjauan pustaka, data dikumpulkan dari artikel ilmiah, buku, dan publikasi akademik yang berkaitan dengan integrasi ilmu pengetahuan dan agama, khususnya yang berfokus pada perspektif Nurcholis Madjid. Proses pengumpulan data melibatkan pencarian sistematis di basis data akademik dan perpustakaan, kemudian dianalisis secara tematik melalui pengkodean, pengkategorian, dan sintesis untuk mengidentifikasi pola-pola yang mendukung integrasi dalam kurikulum. Temuan menunjukkan bahwa penerapan konsep integrasi di UIN Sunan Ampel memperkaya ilmu Islam dan membentuk mahasiswa yang adaptif terhadap perkembangan zaman. Kesimpulannya, integrasi ilmu pengetahuan dan agama meningkatkan relevansi pendidikan Islam masa kini dan mendorong masyarakat yang lebih toleran serta inklusif.